2008
DOI: 10.1121/1.2828213
|View full text |Cite
|
Sign up to set email alerts
|

An echolocation visualization and interface system for dolphin research

Abstract: The present study describes the development and testing of a tool for dolphin research. This tool was able to visualize the dolphin echolocation signals as well as function as an acoustically operated "touch screen." The system consisted of a matrix of hydrophones attached to a semitransparent screen, which was lowered in front of an underwater acrylic panel in a dolphin pool. When a dolphin aimed its sonar beam at the screen, the hydrophones measured the received sound pressure levels. These hydrophone signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…For example, animals trained to use a touchscreen using their nose (American black bear, Ursus americanus: ; dog, Canis lupus familiaris: Range, Aust, Steurer, & Huber, 2008) and tongue (sun bear, Helarctos malayanus: Perdue, 2016). Dolphins can make selections from a computerized "menu" by directing their echolocative clicks towards projected symbols rather than making physical contact with the screen (Amundin et al, 2008). Even very small, nocturnal primate species can be trained to use touchscreens: Joly, Ammersdörfer, Schmitke, and Zimmermann (2014) reported that it took less than 25 days to train naïve grey mouse lemurs (Microcebus murinus) to use touchscreens in a nocturnal set-up.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, animals trained to use a touchscreen using their nose (American black bear, Ursus americanus: ; dog, Canis lupus familiaris: Range, Aust, Steurer, & Huber, 2008) and tongue (sun bear, Helarctos malayanus: Perdue, 2016). Dolphins can make selections from a computerized "menu" by directing their echolocative clicks towards projected symbols rather than making physical contact with the screen (Amundin et al, 2008). Even very small, nocturnal primate species can be trained to use touchscreens: Joly, Ammersdörfer, Schmitke, and Zimmermann (2014) reported that it took less than 25 days to train naïve grey mouse lemurs (Microcebus murinus) to use touchscreens in a nocturnal set-up.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, here we wish focus on improving the affordances of devices for Animal Computer Interaction (ACI), as opposed to focusing primarily on animals using machines in an aid to understanding animal cognition [6,26,29]. Amundin et al [2] explain a very interesting system for dolphins to interact with using echolocation, like our system it is a type of touchscreen. Amundin's was built to work with dolphins, and tested to provide insight into how dolphin might best use a touchscreen system..…”
Section: Background and Related Workmentioning
confidence: 95%
“…The echolocation signals of dolphins are recorded with hydrophones when those clicks are aimed at Frontiers in Ecology and Evolution | www.frontiersin.orga semitransparent screen. Subsequently, the recorded acoustic signals are translated into a corresponding visual image that is projected on the location where the echolocation signals contact the screen: this leads to immediate visual feedback (Amundin et al, 2008). Another approach is eavesdropping on echolocation signals of conspecifics (reviewed in Gregg et al, 2007).…”
Section: Perspectives On Auditionmentioning
confidence: 99%
“…With regards to echolocation, there is an approach that might yield some insightful results: the "echolocation visualization and interface system, " which can visualize echolocation signals and be used as an "acoustically operated 'touch screen"' (Amundin et al, 2008). The echolocation signals of dolphins are recorded with hydrophones when those clicks are aimed at Frontiers in Ecology and Evolution | www.frontiersin.orga semitransparent screen.…”
Section: Perspectives On Auditionmentioning
confidence: 99%